Effect of compatibiliser on the accelerated weathering performance of polypropylene-silica nanocomposites - Anis Sofiah, M. K. (Animo Repository, 2014)
The specimens prepared in this study were melt blended of neat polypropylene (PP), PP/nanosilica (2 wt%), and PP/nanosilica with 3 wt% of PP grafted maleic anhydride (PP-g-MA). The nanocomposites were placed in the accelerated weathering test (AWT) chamber for 200 hours composed of alternating 8 hours of ultra violet (UV) exposure and 4 hours of condensation. The mechanical properties and morphology before and after exposure to AWT specimens were determined using a tensile test instrument and field emission scanning electron microscope (FESEM). Results showed that the weathered specimens with PP-g-MA compatibilizer have higher tensile strength and higher modulus of elasticity than the weathered specimens without the compatibilizer. Moreover, FESEM images showed less cracking and deformation on the fractured surface of exposed nanocomposites with PP-g-MA. It was concluded that the addition of PP-g-MA led to an increased compatibility of matrix and nanofiller, and further improved the weather resistance of nanocomposites. © 2014 W. S. Maney & Son Ltd.